Public Open Space Based On Place Identity (Case Study : Merdeka Square) - Ulfa, Afifah; Ginting, Nurlisa; Marisa, Amy (International Journal of Architecture and Urbanism, 2026)
Public open space has a very high role for the city community, apart from being related to the physical environment, public open space functions as a variety of social and cultural meanings at a very high level. Public open space can be seen based on the identity place. There are four aspects that can from the identity of a place, namely: sustainability, self_esteem, self_ability, and uniqueness in the Merdeka square. This namely accessibility, comfort, activity, and social interaction. The findings show that the merdeka squareas a public open space already contains the identity of the place. However, there are many problems with the arrangement of the merdeka square area which is still lacking, causing the view that binds the merdeka square area to be invisible. Therefore, the government must improve the arrangement of the area so that it blends with the identity of the place around it.